Ecological risk of microplastic toxicity to earthworms in soil: A bibliometric analysis - Guo, Sen; Wang, Qiong; Li, Zishuang; Chen, Yanhua; Li, Hongjie; Zhang, Jiajia; Wang, Xuexia; Liu, Jiawei; Cao, Bing; Zou, Guoyuan; Zhang, Baogui; Zhao, Meng (Frontiers in Environmental Science, 2023)
Accumulation of microplastic (MP) contamination in soil is a serious environmental concern. The addition of exogenous MPs can alter soil structure, physicochemical properties, and material transport. MP is particularly toxic to earthworms, which are considered soil ecosystem engineers, and exacerbates ecological risks; however, there is a lack of comprehensive and in-depth analyses of how MPs enhance earthworm toxicity. In this study, we report a bibliometric analysis of 77 peer-reviewed papers published before December 2021 that aimed to systematically analyze how the addition of exogenous MPs contributes to earthworm toxicity and clarify the developmental lineage and research hotspots in this field. The results show that: (1) Polyethylene and polystyrene are the most representative materials used to study the toxic effects of MPs on earthworms. (2) The toxic mechanisms of MPs on earthworms mainly involve histopathological damage and oxidative stress as well as serving as carriers of complex pollutants (e.g., heavy metals and organic pollutants) through combined adsorption-desorption processes. (3) Oxidative stress is the typical reaction process of MP toxicity in earthworms. When the content of MPs in soil exceeds 0.1%, earthworm growth is affected and oxidative stress is induced, which results in neural and DNA damage. Based on the existing literature, the prospects for future research on the ecological risks posed by MP to earthworms have also been discussed. Overall, this study helps clarify the ecological risk of soil MP toxicity to earthworms, reveals the mechanism of their toxic effects, and provides a theoretical basis for building a healthy and ecologically sustainable soil environment.